Kenya : Sub-file A: Johnstone Kenyatta - Great Britain; National Archives (Great Britain); Adam Matthew Digital (Adam Matthew Digital, 1929)
Government memos and other communications relating to the visit to London in 1929 of Johnstone [Jomo] Kenyatta, secretary of the Kikuyu Central Association, and associated topics such as the Native Lands Trust Bill